PENCIPTAAN KOMIK BEBER - Indiria Maharsi (Institut Seni Indonesia Yogyakarta, 2012)
Beber Comic isa comic that combine the concept of modern comic and Wayang Beber as theembryo of the embryo of the modern comic. It is an innovation considering that in the development ofmodern comic it has never been noted such a form/style of comic. This combination is a credit for WayangBeber as a magnificent cultural inheritance of Indonesia. It is also an effort revitalize Wayang Beber.The title of the Beber Comic created is PangeranAntaguna. It is a story of a man's hard journey infinding who he really is and the meaning of life. The visual concept is combining the elements ofWayangBeber and of modern comic. It results in a unique comic form/ style. HopefUlly, the innovation of BeberComic will stimulate comic creators and will positively support the development of comic in the fUture.Keywords: Beber comic, new innovation.